Frequency of Congenital Cardiac Malformations in the Neonates with Congenital Hypothyroidism - yazdan ghandi; Seyyed Amir Sanatkar; Danial Habibi; Fatemeh Dorreh; Bahman Sadeghizadeh (Mashhad University of Medical Sciences, 2018)
Background: Congenital hypothyroidism (CH) is a prevalent disorder, which is associated with several other congenital anomalies, especially cardiac diseases. The present study aimed to determine the prevalence of congenital heart disease (CHD) in the neonates with CH.Methods: This cross-sectional study was conducted on two groups of 79 subjects to compare the type and frequency of congenital cardiac anomalies between the neonates with the confirmed diagnosis of CH (TSH≥10 mlU/ml) and healthy infants. The study was performed in Kowsar Clinic affiliated to Arak University of Medical Sciences, Iran. Level of thyroid-stimulating hormone (TSH) was measured within days 3-7 of birth using the samples collected from the soles of the neonates. In addition, all the subjects were evaluated for the presence of CHD using echocardiography before day 30 of life.Results: In total, 79 neonates were enrolled in the study. The case group consisted of 34 females (43.04%) and 45 males (53.96%), and the control group consisted of 43 females (54.43%) and 36 males (45.57%). The groups were matched in terms of age and gender. Cardiac involvement was only detected in the case group (CH infants) with the prevalence of 22.7%. Among the non-cyanotic malformations observed in the case group, one infant had ventricular septal defect (1.3%), eight infants had atrial septal defect (10.1%), three infants had patent ductus arteriosus (3.8%), three neonates had endocardial cushion defect (3.8%), two neonates had pulmonary stenosis (2.5%), and one infant had dilated cardiomyopathy (1.3%). Moreover, six neonates were diagnosed with Down syndrome. All the infants with endocardial cushion defect (n=3) had Down syndrome, and no significant association was observed between TSH and thyroxine (T4) in the presence of CHD.Conclusion: According to the results, the high prevalence of cardiac malformations in the neonates with CH necessitated cardiac examinations using echocardiography.